Fabrication and Characterization of CuInSe2 Thin Film Applicable for a Solar Energy Light Absorption Material via a Low Temperature Solid State Reaction - Kuo-Chin Hsu; Yaw-Shyan Fu; Pei-Ying Lin; I-Tseng Tang; Jiunn-Der Liao (International Journal of Photoenergy)
The chalcopyrite CuInSe2 thin film synthesized via a low temperature solid state reaction from CuSe and InSe powders was investigated using X-ray diffractomy (XRD), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), transmission electron microscopy (TEM), and UV-vis absorption spectroscopy. CuSe and InSe phases react and directly transform into CuInSe2 without the occurrence of any intermediate phase. The morphology of the newly formed CuInSe2 crystalline was close to that of the CuSe reactant particle based on the TEM results, which indicate that the solid state reaction kinetics may be dominated by the In3+ ions diffusion. The CuInSe2 thin film prepared from the solid state reaction did not use the selenide process; its band gap might reach 1.06 eV, which is competent and suitable to be used for a thin film solar cell light absorption layer.